2008
DOI: 10.1002/cmr.b.20101
|View full text |Cite
|
Sign up to set email alerts
|

Design and construction of a microcoil NMR probe for the routine analysis of 20‐μL samples

Abstract: Recent advances in microcoil NMR have provided commercially available, robust methodologies for analyzing mass and volume limited samples in the low microliter regime, and the technology has been applied in a number of areas. Unfortunately, due to constraints on sample size and the limited solubility of some compounds of interest, the application of this approach to certain areas of development, such as the structural analysis of chromatography eluates, is restricted. A current challenge is to provide an optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…MS can be used for confirmation of the isolated peaks before further characterization by NMR (Babjak et al, 2002). With the advances in NMR technologies, for example, introduction of flow probes to allow for LC-NMR analysis, higher sensitivity probes based on the use of microcoils (Olsen et al, 1995;Lacey et al, 2001;Henry et al, 2008) and cryocooling of the active probe (Keun et al, 2002;Rashid et al, 2002) the power of both MS and NMR can be coupled for more complete impurity profiling. Mistry et al (1997), have shown how this methodology can reduce time-consuming isolation of individual impurities and eliminate the potential for degradation during the work-up process.…”
Section: Identification Of Process Impurities and Degradation Promentioning
confidence: 99%
“…MS can be used for confirmation of the isolated peaks before further characterization by NMR (Babjak et al, 2002). With the advances in NMR technologies, for example, introduction of flow probes to allow for LC-NMR analysis, higher sensitivity probes based on the use of microcoils (Olsen et al, 1995;Lacey et al, 2001;Henry et al, 2008) and cryocooling of the active probe (Keun et al, 2002;Rashid et al, 2002) the power of both MS and NMR can be coupled for more complete impurity profiling. Mistry et al (1997), have shown how this methodology can reduce time-consuming isolation of individual impurities and eliminate the potential for degradation during the work-up process.…”
Section: Identification Of Process Impurities and Degradation Promentioning
confidence: 99%
“…Further optimization of the probe circuitry will lead to a more effective cancellation without the need to weight the protein concentrations, and better resolution for more complex systems. The use of an increased solenoidal coil sample volume [32] would improve the concentration sensitivity of the method. Additionally, while we used a series of shaped Gaussian pulses for the saturation in order to follow the approach of Meyers et al , the substitution of a long soft pulse could potentially achieve the same level of irradiation while eliminating the extra time involved with optimizing the parameters for the shaped pulses.…”
Section: Discussionmentioning
confidence: 99%
“…The on-line LC-NMR mode requires the use of a continuous-flow probe with a suitably matched sample detection volume to provide sufficient sensitivity for low concentration analyte detection. 53 Pre-concentration systems prior to NMR detection including SPE and column trapping 88 offer clear advantages in signal enhancement. Further, incorporation of a cryo-flow probe for such applications not only increases the sensitivity but also allows for rapid characterization of metabolites.…”
Section: Methods To Enhance Resolution and Sensitivitymentioning
confidence: 99%